Expressive and literary resources in the Ancash huayno - Julca Guerrero, Félix (2019)
This paper describes and analyzes, from the linguistic and literary perspectives, the expressive, literary and linguistic-communicative resources in the Ancash huayno, a traditional Andean manifestation in which Quechua folk poems and traditional rural music are combined. The research was descriptive and approached with a qualitative approach. The data collected demonstrates that the Quechua verbal art in the Ancash Huayno evidences the use of different lexical, expressive-communicative and literary resources to manifest different aspects of life, death and love with its many facets. In the composition of the verses it is evident processes of resemantization and new semantic turns that acquire words and expressions, use of linguistic loans and code switching, expressed poetically and metaphorically. In this way, the Ancash huayno songs poetically and artistically interprets the feelings and experiences of its people and constitutes the Ancash cultural richness.